It is Harder, not Easier, to Predict the Winner of the Champions League - Jeroen Schokkaert; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
European Cup football has experienced a major change in firmat with the introduction of the Champions League in 1992 and a major change in admission rules with direct qualification for multiple teams from the highest ranked leagues in 1999. We show that, in line with popular press reports and other studies, qualification in lower rounds has become more predictable in the Champions League. At the same time, however, outcomes at later stages have become less predictable. We provide evidence and an explanation.
Keywords: L83; 330; Champions League; European Cup; Sports Tournaments; Uncertainty of Outcome; Fußballsport; Markovscher Prozess; Schätzung; Europa